Zoledronic acid promotes osteoclasts ferroptosis by inhibiting FBXO9-mediated p53 ubiquitination and degradation - Xingzhou Qu; Zhaoqi Sun; Yang Wang; Hui Shan Ong (PeerJ, 2021)
Bisphosphonates (BPs)-related osteonecrosis of jaw (BRONJ) is a severe complication of the long-term administration of BPs. The development of BRONJ is associated with the cell death of osteoclasts, but the underlying mechanism remains unclear. In the current study, the role of Zoledronic acid (ZA), a kind of bisphosphonates, in suppressing the growth of osteoclasts was investigated and its underlying mechanism was explored. The role of ZA in regulating osteoclasts function was evaluated in the RANKL-induced cell model. Cell viability was assessed by cell counting kit-8 (CCK-8) assay and fluorescein diacetate (FDA)-staining. We confirmed that ZA treatment suppressed cell viability of osteoclasts. Furthermore, ZA treatment led to osteoclasts death by facilitating osteoclasts ferroptosis, as evidenced by increased Fe2+, ROS, and malonyldialdehyde (MDA) level, and decreased glutathione peroxidase 4 (GPX4) and glutathione (GSH) level. Next, the gene expression profiles of alendronate- and risedronate-treated osteoclasts were obtained from Gene Expression Omnibus (GEO) dataset, and 18 differentially expressed genes were identified using venn diagram analysis. Among these 18 genes, the expression of F-box protein 9 (FBXO9) was inhibited by ZA treatment. Knockdown of FBXO9 resulted in osteoclasts ferroptosis. More important, FBXO9 overexpression repressed the effect of ZA on regulating osteoclasts ferroptosis. Mechanistically, FBXO9 interacted with p53 and decreased the protein stability of p53. Collectively, our study showed that ZA induced osteoclast cells ferroptosis by triggering FBXO9-mediated p53 ubiquitination and degradation.